PENGARUH LATIHAN DRILL DAN LATIHAN POLA PUKULAN TERHADAP KEMAMPUAN SMASH BULUTANGKIS PADA PB LIANSA JUNIOR MASBAGIK LOMBOK TIMUR TAHUN 2019 - Intan Primayanti; Isyani Isyani (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The aims  of this study is to determine the effect of the drill exercise and the smash pattern toward the accuracy of smash on badminton athletes of PB Liansa Junior Masbagik East Lombok in 2019. This study uses the experimental method with the design of two groups pre-test-post-test design. The population in this study is the athlete of PB. Liansa Junior Masbagik East Lombok in 2019 which amounted to 27 players. The sampling technique used the purposive sampling, with criteria that is: (1) the attendance is at least 75% (active to follow exercise), (2) players are athletes of badminton PB Liansa Junior Masbagik East Lombok 2019, (3) aged 10-12 years old (junior), (4) male, (5) training duration is least 3 months. There were 18 athletes who met the criteria. The instrument used is the smash accuracy test from PBSI (2006: 36). Data analysis used t-test formula. The result of research shows that: (1) There is effect of drill exercise toward smash accuracy on badminton athletes of PB Liansa Junior Masbagik East Lombok in 2019, with t score 14.473 > t-table 2.31 and significance value of 0,000 <0.05, with percentage increase of 61,02%. (2) There is effect of the smash pattern exericise on the smash accuracy on badminton athletes of PB Liansa Junior Masbagik East Lombok in 2019, with t score 11.701 > t table 2.31, and significance value of 0,000 < 0.05, with percentage increase equal to 46.43%. (3) the drill exercise is more effective toward the accuracy of smash on badminton athletes of PB Liansa Junior Masbagik East Lombok in 2019 than the smash pattern exercise, with posttest average difference of 2.889.